2021
DOI: 10.1007/s10554-021-02498-4
|View full text |Cite
|
Sign up to set email alerts
|

Biventricular myocardial function in Covid-19 recovered patients assessed by speckle tracking echocardiography: a prospective cohort echocardiography study

Abstract: Although severe acute respiratory syndrome coronavirus 2 causes respiratory disease, it may also lead to cardiovascular involvement with unknown long-term consequences. The aim of our study was to evaluate prospectively cardiac involvement in patients after the recovery from Covid-19, using two-dimensional speckle tracking echocardiography. 100 Covid-19 recovered patients with preserved left ventricular ejection fraction, were included, divided based upon clinical manifestation into two groups, those who were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
9
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
5
9
1
2
Order By: Relevance
“…These data indicate that COVID-19 patients may have subclinical left ventricular dysfunction and that those that are critically ill may have a greater decline in cardiac dysfunction. These data are consistent with other studies that demonstrated a reduction in LVGLS in COVID-19 patients [ 16 , 17 ]. In addition, we found that a reduced LVGLS was associated with an increased risk for mortality.…”
Section: Discussionsupporting
confidence: 93%
“…These data indicate that COVID-19 patients may have subclinical left ventricular dysfunction and that those that are critically ill may have a greater decline in cardiac dysfunction. These data are consistent with other studies that demonstrated a reduction in LVGLS in COVID-19 patients [ 16 , 17 ]. In addition, we found that a reduced LVGLS was associated with an increased risk for mortality.…”
Section: Discussionsupporting
confidence: 93%
“…The findings of this late study are more similar to our study. Similar differences can be observed in more recent publications [ 39 42 ], with rates of subclinical ventricular in up to one in three hospitalized patients [ 40 ]. The most reasonable explanation for the discrepancies observed between series of post COVID-19 patients are the differences in the severity of the patients included in them.…”
Section: Discussionsupporting
confidence: 89%
“…It is notable that although some authors have reported major cardiac abnormalities after recovery of COVID-19 infection, such as depressed LVEF [45], pericarditis, and pericardial effusion [46,47], these findings have not been detected in most majority of publications to date [5,[36][37][38][39][40][41][42]. A possible explanation for these findings is that these are predominantly case reports or case series with small sample size.…”
Section: Discussionmentioning
confidence: 98%
“…It has been postulated that SARS-CoV-2 receptor distributions between two ventricles are not equivalent, with the lateral segment of the left cardiac ventricle having the most viral receptors [10]. However, our ndings contrast with a study byTryfou et al which reported a signi cant decrease in RV-FWS values in severe COVID-19 subjects compared to the healthy population (− 18.17 ± − 3.32 vs. − 26.03 ± − 4.55%, p < 0.0001) [11]. Nevertheless, it is important to note that the echocardiograph measurement in the study as mentioned above was conducted 30 days after admission, while our study conducted the measurement after 12 weeks.…”
contrasting
confidence: 99%